Assessing sedimentation equilibrium profiles in analytical ultracentrifugation experiments on macromolecules: from simple average molecular weight analysis to molecular weight distribution and interaction analysis - Harding, Stephen E.; Gillis, Richard B.; Adams, Gary G. (Springer Verlag, 2016)
Molecular weights (molar masses), molecular weight distributions, dissociation constants and other interaction parameters are fundamental characteristics of proteins, nucleic acids, polysaccharides and glycoconjugates in solution. Sedimentation equilibrium in the analytical ultracentrifugation provides a powerful method with no supplementary immobilization, columns or membranes required. It is particularly powerful when used in conjunction with its sister technique, namely sedimentation velocity analysis. We describe key approaches now available and their application to the characterisation of antibodies polysaccharides and glycoconjugates. We indicate how major complications such as thermodynamic non-ideality can now be routinely dealt with, thanks to a great extent to the extensive contribution of Professor DonWinzor over several decades of research.